Enforcement-Prevention Asymmetry in State Financial Accountability: Empirical Evidence of Risk Management Decoupling with an Islamic Ethical Perspective - Anggi Miharsa Putri; Rien Agustin Fadjarenie (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2026)
Introduction: Indonesia’s post-pandemic economy demands increasingly higher state financial accountability to safeguard public wealth (hifz al-mal); however, a paradox emerges as governance infrastructure becomes more comprehensive while the Corruption Perception Index declines and corruption cases have increased during 2020–2023. This study aims to analyze the effects of corruption control effectiveness, Government Internal Control System maturity, risk management, and internal auditor capability on state financial accountability through an Islamic ethical governance lens. Methods: A mixed-method convergent design was employed, combining quantitative panel data regression using the Fixed Effect Model on 81 ministries/agencies for the 2021–2024 period (N = 324) with qualitative analysis based on in-depth interviews with six key informants from key oversight institutions. Results: The findings indicate that internal auditor capability, internal control system maturity, and corruption control effectiveness have positive and significant effects on accountability, whereas risk management shows no significant effect. Qualitative results confirm the dominance of enforcement mechanisms and reveal that risk management practices remain siloed and compliance-driven, highlighting a phenomenon of ethical decoupling. Conclusion: These findings demonstrate an enforcement-prevention asymmetry, where mechanisms based on active monitoring and sanctions are more effective than preventive system-based approaches. From an ethical governance perspective, this condition reflects the limited internalization of accountability values such as amanah (trust), indicating that accountability remains externally driven resembling formal hisbah (external enforcement)—rather than intrinsically embedded. Strengthening public financial governance therefore requires not only formal institutional improvements but also the integration of ethical responsibility and anti-israf (anti-wastefulness) behavior to achieve more substantive and sustainable accountability.